Fedir Mykolayovych Lyman (22.02.1941–13.06.2020) (Algebra and Discrete Mathematics, 2020)
The famous Ukrainian mathematician and educator, Doctor of Physical and Mathematical Sciences, Professor Fedir Mykolayovych Lyman passed away on June 13, 2020 after a long illness.